The role of continuous education and training in improving hospital nurse performance: case study of employee development program implementation - Aziz, Abdul (Universitas Aisyah Pringsewu, 2023)
Continuous education and training play an important role in improving the performance of hospital nurses, which in turn has a positive impact on the quality of health care. This research aims to investigate the key role of continuing education and training in the healthcare context and explore the challenges, strategies, and impacts of its implementation. A descriptive qualitative approach was used with data obtained from relevant previous research results. The research results show that continuous education and training enable nurses to become leaders in best practices, contribute to innovation, and play an important role in improving the quality of health care. The importance of integrating these programs into organizational culture and management and maintaining sustainability through incentives, evaluation, and innovation is also highlighted in this research. This research provides important insights into the strategic role of continuing education and training in improving health care and how hospitals can ensure its sustainability for the benefit of patients and nursing staff.